2018
DOI: 10.1016/j.icarus.2018.02.004
|View full text |Cite|
|
Sign up to set email alerts
|

Seasonal stratospheric photochemistry on Uranus and Neptune

Abstract: A time-variable 1D photochemical model is used to study the distribution of stratospheric hydrocarbons as a function of altitude, latitude, and season on Uranus and Neptune. The results for Neptune indicate that in the absence of stratospheric circulation or other meridional transport processes, the hydrocarbon abundances exhibit strong seasonal and meridional variations in the upper stratosphere, but that these variations become increasingly damped with depth due to increasing dynamical and chemical time scal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
145
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(154 citation statements)
references
References 96 publications
(214 reference statements)
9
145
0
Order By: Relevance
“…They argued that the discrepant supersaturated mole fraction may have instead indicated spatial heterogeneities in stratospheric methane abundance or temperatures, noting that the Hershchel data probed more global conditions while the Spitzer data were biased towards warmer temperature regions. Interestingly, our data indicate a factor of 5-6 enrichment in acetylene in precisely the coldest regions (i.e., midlatitudes) while mole fraction at warm equatorial regions remain in strong agreement with values derived from Spitzer (Orton et al 2014a;Moses et al 2018), consistent with proposed explanation for the observed discrepancy.…”
Section: Nature Of the 13-µm Emissionsupporting
confidence: 90%
See 4 more Smart Citations
“…They argued that the discrepant supersaturated mole fraction may have instead indicated spatial heterogeneities in stratospheric methane abundance or temperatures, noting that the Hershchel data probed more global conditions while the Spitzer data were biased towards warmer temperature regions. Interestingly, our data indicate a factor of 5-6 enrichment in acetylene in precisely the coldest regions (i.e., midlatitudes) while mole fraction at warm equatorial regions remain in strong agreement with values derived from Spitzer (Orton et al 2014a;Moses et al 2018), consistent with proposed explanation for the observed discrepancy.…”
Section: Nature Of the 13-µm Emissionsupporting
confidence: 90%
“…Higher in the stratosphere, our comparison is limited to a span of nine years. This span is short compared to estimates of long radiative and dynamical timescales on Uranus (Conrath et al 1990;Moses et al 2018), and so it is unsurprising to find little change in the northern hemispheric emission at 13 µm. By the same token, it would be surprising if any physical process could produce the the apparent discrepancies between the 2018 data and 2009 model, further suggesting that this is likely attributable to an error in the assumed profiles of temperatures or acetylene abundances at higher altitudes that go into producing the forward model.…”
Section: Seasonal Changesmentioning
confidence: 89%
See 3 more Smart Citations